KAJIAN PERENCANAAN PLTS TERHUBUNG KE GRID UNTUK MELAYANI SUPLAI DAYA LISTRIK DI MENARA STT - PLN - Dewi Purnama Sari; Novi Kurniasih; Agus Yogianto (Sekolah Tinggi Teknik - PLN, 2018)
In this research discusses about PLTS planning studies connected to grid to serve electrical power supply in STT–PLN tower. During this STT–PLN tower get electrical power supply sourced from PLN only where the capacity of power installed 1100 kVA with transformer capacity equal to 1250 kVA. The distribution of electrical power to the STT–PLN tower is obtained from Tolimo feeder which is connected directly to Duri Kosambi 192 Baru substation. So for that in this research made a planning of distribution of electrical power distribution with PLTS – Grid systems where PLTS system serve the use of electricity load from 08.00 WIB – 17.00 WIB, the rest only relies on electricity source from PLN. With PLTS – Grid system, the use of batteries can be eliminated. The electrical loads connected to the PLTS system and grid use the same energy as those supplied by the PLTS for a certain period of time. In this case, the grid becomes a storage or lender temporary for the fulfillment of electrical power demand. So with the application of this concept we only spend the investment cost of the PLTS system without batteries and the cost of leasing the network in the PLTS – Grid system.